Electrochemical B−H Nitrogenation: Access to Amino Acid and BODIPY‐Labeled nido‐Carboranes. Issue 3 (17th November 2020) - Yang, Long; Bongsuiru Jei, Becky; Scheremetjew, Alexej; Kuniyil, Rositha; Ackermann, Lutz
Abstract: Electrocatalyzed oxidative B−H nitrogenations of nido ‐carborane ( nido ‐7, 8‐C2 B9 H12 − ) with N‐heterocycles have been established, enabling the preparation of various N‐substituted nido ‐carboranes without chemical oxidants or metal catalyst under ambient conditions. The electrolysis manifold occurred with high levels of efficiency as well as chemo‐ and position‐ selectivity, employing sustainable electricity as the sole oxidant. The strategy set the stage for a user‐friendly access to novel amino acid and fluorogenic boron‐dipyrrin (BODIPY)‐labeled nido ‐carborane hybrids. Abstract : Metal‐free electrocatalyzed B−H nitrogenation is used to synthesize various N‐heterocyclic nido ‐carboranes.